Motociclistas : perfil, prevalência de uso da moto e acidentes de trânsito - estudo de base populacional - Seerig, Lenise Menezes (2012)
A cross sectional populational study was performed in Pelotas, Southern Brazil, aiming to describe the profile of motorcycle users, determine the prevalence and type of use and to report the acidentes with body injury happened in the last 12 months. Sampling process was carried out in two stages, with the primary unit being the census track and the secondary the house. The study included 3,004 individuals aged 10 to 59 years old, residents in urban zone, which answered a structured questionnaire. The outcome of the study was the use of motorcycle (driver or as a ride. The independent variables investigated were sex, age (complete years), skin color, educational level (complete years of study) and socioeconomic level (measured in quintiles). The descriptive analyses used the Stata 12 software, with the svy command for conglomerates. The prevalence of motorcycle use was 25.1% (95% CI 95% 22.6-27.60). The major part of the drivers was composed by males (79%), while women were the majority in the ride condition (73%). In relation to the age, teenagers (10-17 years) used the motorcycle predominately in the ride condition (23.1%). Around 40% of the users were not wearing the jugular belt appropriately and the majority (75.9%) reported to have a very high risk of motorcycle accident. In relation to the accidents, the overall prevalence was 8% (95%CI 5.6-10.3), being higher among male aged 18 to 35 years. Considering our results, it was possible to conclude that the use of motorcycle has not a specific niche and public policies aiming to prevent accidents should be directed to the general population.